Validation and modification of dried blood spot‐based glycosylated hemoglobin assay for the longitudinal aging study in India. Issue 4 (3rd December 2014) - Hu, Peifeng; Edenfield, Michael; Potter, Alan; Kale, Varsha; Risbud, Arun; Williams, Sharon; Lee, Jinkook; Bloom, David E.; Crimmins, Eileen; Seeman, Teresa
<x xml:space="preserve">Abstract</x> Objectives This study aims to validate a modified dried blood spot (DBS)‐based glycosylated hemoglobin (HbA1c) assay protocol, after a pretest in India showed poor correlation between the original DBS‐based protocol and venous results. Methods The original protocol was tested on different chemistry analyzers and then simplified at the University of Washington (UW). A second pretest was conducted in India to validate the modified assay protocol, using 44 quality control specimens. Results Data from UW indicated that, using the original protocol, the correlation coefficients between DBS and venous results were above 0.98 on both Bio‐Rad and Olympus chemistry analyzers. The protocol worked equally well on filter paper, with or without pre‐treatment, and when the recommended amount of blood spot material, or less, was used. A second pretest of the modified protocol confirmed that DBS‐based levels from both Olympus and Roche chemistry analyzers were well correlated with DBS results from UW (correlation coefficients were above 0.96), as well as with venous values (correlation coefficients were above 0.94). Conclusions The DBS‐based HbA1c values are highly correlated with venous results. The pre‐treatment of filter paper does not appear to be necessary. The poor results from the first pretest are probably due to factors unrelated to the protocol, such as problems with the chemistry analyzer or assay reagents. Am. J. Hum. Biol. 27:579–581, 2015. © 2015 Wiley Periodicals, Inc.